Sigma Class: Program Pembelajaran Interaktif sebagai Upaya Pengenalan Literasi Data bagi Siswa Pendidikan Dasar: Sigma Class: An Interactive Learning Program to Introduce Data Literacy for Primary School Students - Adzim, Muhammad Fauzan; Rahmi, Hendryati; Primasdali, Indah; Mahfudzi, Muhammad Ferry; Nasywani, Nur; Fatmada, Srikandi Aristawati Hanny Nur; Maisarah, Maisarah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Primary education is the foundation for developing critical, analytical, and logical thinking skills, making early strengthening of data literacy essential to help students understand, manage, and present information meaningfully. This article examines the implementation of Sigma Class as a program to introduce data literacy through interactive learning for grade five and grade six students in Kelurahan Palam, aiming to build a basic understanding of primary and secondary data and the presentation of data in tables, bar charts, and pie charts. The program was designed as activity-based learning that combines material exposition with a data-generating game and a voting activity, supported by tutor facilitation and an individual ten-item assessment at the end of each session. The activity involved 131 students from four schools, with each meeting lasting approximately 90 minutes. Results show an overall average score of 84.89, with the highest average of 90.87 in one class and the lowest average of 76.25 in another class within the same school, and all class averages exceeding each school's minimum mastery criteria. The findings affirm the effectiveness of activity-based and game-supported approaches for introducing data literacy, while also indicating the need to strengthen prerequisite arithmetic and to differentiate instructional strategies so that outcomes become more even across classes.